The truth about trade : the real impact of liberalization - George, Clive (Zed Books ; Distributed in the USA exclusively by Palgrave Macmillan, 2010)
Clive George's book examines the evidence both for and against world trade. He exposes the myths, and presents challenging new proposals for comprehensive reform.